Sosialisasi Pemanfaatan Limbah Pertanian Sebagai Sumber Pakan Alternatif Di Kelompok Pkk Desa Batu Belah. - Jati, Putri Zulia; Rianita, Resti (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2022)
Community service activities are a form of the Tridharma of Higher Education carried out by the service team with partners, namely the PKK Group of Batu Belah Village, Kampar District, Kampar Regency. This service aims to increase community knowledge about the utilization of agricultural waste as a source of animal feed is needed to be able to provide feed continuously with good quality. The method used is in the form of material delivery by resource persons and discussions. This training was attended by mothers of the Batu Belah PKK Group. This training was carried out in a democratic manner through adult education methods, where the service team was only a facilitator in problem solving. While the assistance focused on lectures, questions and answers, practice and discussion. The lecture method was used to present the material that had been prepared by the Implementation Team and direct practice. After that, the results of observation and evaluation of activities from these findings can be concluded that training activities have benefits and enthusiasm of the community, especially in the utilization of agricultural waste as an alternative source of feed.